A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae) - Prokofiev, Artem M.; Gon, Ofer; Psomadakis, Peter N. (Zootaxa, 2016)
A new species of Neobathyclupea is described from two specimens collected off Myanmar and off Socotra Island. The new species is most similar to N. malayana, but differs from it and other congeners in having jet-black coloured fins, larger pseudobranch, dorsal-pterygiophore pattern and some body proportions. Neobathyclupea malayana is re-diagnosed. Individual variations in armament of the preopercle and in the dorsal-pterygiophore patterns within Bathyclupeidae are discussed.